Effects of grip waxing on ski and pole forces in diagonal skiing - Ishikawa, M.; Vähäsöyrinki, P.; Komi, P.; Kolehmainen, V.; Salmi, J.; Linnamo, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The friction between Ski and snow is an important element to accelerate the kick of the stance phase of classicai technique cross-country (x-c) skiing. It has been shown that with increasing skiing speed, the pole force contribution decreased (Vähäsöyrinki et al, submitted). However, relatively little is known how skiers compensate the x-c ski locomotion under different wax conditions. The purpose of the present study was to examine effects of different grip wax on the pole and ski forces together with muscle activities.